Penerapan Model Pembelajaran Project Based Learning Terhadap Problem Solving Skills Peserta Didik - Uji Abu Tholib; Rugaiyah Rugaiyah (Peneliti.net, 2022)
Educators and students are the two main components that determine the success of the teaching and learning process in the education unit. The success of the teaching and learning process can be perceived from the increase of students’ ability which is not only discerned from measuring academic values and knowledge but also includes other components, such as skills, talents, critical thinking skills and problem solving. Basically, education aims to make students ready to face the world of globalization which is full of challenges in the 4.0 revolution era and be able to answer challenges appropriately both at the national and international levels. The purpose of this research is to use a systematic method to review the literature on applying project-based learning models to students' problem-solving skills. This research uses a qualitative descriptive approach with a literature study. Data is collected by reviewing accredited articles and journals from the Google Scholar website, Publish and Perish apps. The study results show that the application of the project-based learning model to students can make the learning process for students effective and efficient. Because involving learning in a real and contextual way, it produces student outputs in the form of the ability to solve problems from various specific and general issues within the student's environment